Digital Doubt and Gendered Moral Policing: Social Media’s Role in Malay Atheist Identity Formation and Its Theological Implications - Kauthar Razali; Nurhanisah Senin; Nur Syahirah Mohammad Nasir; Muhammad Hafizuddin Ghani; Susana Aditiya Wangsanata (Jabatan Usuluddin & Dakwah, Akademi Pengajian Islam, Universiti Malaya, Kuala Lumpur., 2026)
Indexed by Tier 3